MODEL PEMBELAJARAN THINK TALK WRITE DENGAN MEDIA KERTAS TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Laelatun Nahirus Sa'adah (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2020)
This study aims to 1. Describe improvement in students mathematics learning outcomes 2. To describe students responses. The type of research used is classroom action research. The subjects of this study were VII-D class of SMP Negeri 2 Rengel in the academic year 2017/2018 with a total of 32 students consisting of 20 male students and 12 female students. Data collection techniquesin the form of tests and questionnaires. The instrumen used is the test of student learning outcome, student response questionnaires and documentation. The result of the study through the application of learning think talk write with paper media can improve student learning outcomes and get a positive response from students on the subject of VII-D quadrangular flat class building SMP Negeri 2 Rengel 2017/2018 school year can be seen from the average mathematics learning outcomes of students in cycle I, II, III (39.6; 63.77; 75.06). and the avarage response percentage of students gets a positive response avarage of 91.01% and a negative response avarage of 8.99% so that this study is said to get a positive response from studets.